2021
DOI: 10.1093/ajcn/nqaa433
|View full text |Cite
|
Sign up to set email alerts
|

Direct assessment of body iron balance in women with and without iron supplementation using a long-term isotope dilution method in Benin and Switzerland

Abstract: Background Long-term isotopic dilution measurements of body iron may allow quantification of basal body iron balance and iron gains during an iron intervention with higher precision and accuracy than conventional iron indices. Objectives We compared body iron balance before, during, and after oral iron supplementation in women in Benin and in Switzerland. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The study populations, the iron compound provided, the daily iron dose, the daily median iron absorbed and lost per kg BW from our study and all the other long-term isotopic studies with iron supplementation are listed in Table 4. 7,8 There was no significant difference in the distributions of individual daily iron losses between Kenyan and Gambian toddlers (p = 0.09). Expressed in terms of body weight, daily iron loss was correlated significantly with iron absorption (r = 0.66 [95% confidence interval 0.48-0.78]) but not with iron dose (r = 0.16 [95% CI −0.10 to 0.40]) in our study, in Gambian toddlers and in women in Benin and Switzerland.…”
Section: R E Su Ltsmentioning
confidence: 91%
See 3 more Smart Citations
“…The study populations, the iron compound provided, the daily iron dose, the daily median iron absorbed and lost per kg BW from our study and all the other long-term isotopic studies with iron supplementation are listed in Table 4. 7,8 There was no significant difference in the distributions of individual daily iron losses between Kenyan and Gambian toddlers (p = 0.09). Expressed in terms of body weight, daily iron loss was correlated significantly with iron absorption (r = 0.66 [95% confidence interval 0.48-0.78]) but not with iron dose (r = 0.16 [95% CI −0.10 to 0.40]) in our study, in Gambian toddlers and in women in Benin and Switzerland.…”
Section: R E Su Ltsmentioning
confidence: 91%
“…We conducted the study between February and May 2021 in rural Kwale County, Kenya. To study children who had enriched and equilibrated body iron isotopic composition, 2,4,8 we recruited children who previously participated in stable iron isotope studies between July 2019 and January 2020. The designs of the two studies and details of the sample size calculation are provided in Supplemental Material (Data S1).…”
Section: Study Site and Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Under further detailed data extraction for Forest plot generation and further quantitative evaluation, three studies were excluded as two studies did not comprise an adequate control group. In one case, both groups received iron, one with ascorbic acid, the other received iron without ascorbic acid and in the other case, both groups received iron, just different by the place of intervention (Benin and Switzerland) (Speich et al, 2021). The third study excluded was identified to be an outlier under statistical evaluation, excluded by the responsible statistician.…”
Section: Review Of the Evidencementioning
confidence: 99%